THE INTERNAL CIRCULATION OF GOODS IN MOZAMBICAN TERRITORY: A COUNTRY ON WHEELS - Jesus Neto, Antonio Gomes de (GeoTextos, 2017)
Mozambique is historically known for being a territory turned to its exterior, both because it drains the Southern African inner production (especially its neighbors South Africa, Swaziland, Zimbabwe and Malawi) and because its economy has long been directed to the exportation of its domestic production. Even though the current “megaprojects” model stills follows this extraverted logic, since the country’s independence in 1975 the Mozambican government has been making an effort to integrate the territory and set up a national economy. When it comes to the circulation of goods, this task depends on road transport by means of numerous roads (mostly unpaved), normative instruments, regulatory institutions and various transport operators (such as companies, autonomous drivers and informal carriers). Thus, based on Milton Santos’ proposal to understand the geographical space through its technical and political normative dimensions, this article attempts at providing an updated framework for the inner circulation of goods in Mozambique.